Study of the Immunological Status of Children with Acute Stenosing Laryngotracheitis and Correction of Identified Disorders (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The work is devoted to the study of the state of cellular and humoral immunity in acute and recurrent laryngotracheitis in children with a further assessment of the clinical and immunological efficacy of the immunocorrective drug Ergoferon, for which a comprehensive examination and dynamic follow-up of 95 patients with laryngotracheitis were conducted. Cellular suppression and activation of humoral immunity were revealed in patients with OSLT. Patients with frequent relapses of OSLT showed significant increases in IL-4 and IL-1b levels, as well as an imbalance of interferogenesis and an increase in IgE levels. The use of an immunomodulatory drug with antiviral activity "Ergoferon" in the complex therapy of children with OSLT, especially in its recurrent course, has a beneficial effect on the clinical course of the disease, as well as on the immune status of patients.